An Approach on V-Shaped Milling for Rotor Balancing of Armatures - Mengxuan Li; Yuhang Sun; Ruiwen Dong; Weiyu Chen; Dong Jiang (Machines, 2022)
In order to improve the dynamic balancing accuracy of the micromotor armature, a method of V-shaped milling based on a discrete vector model for unbalance correction is proposed. The discrete vector model is fitted according to the parameters of the milling cutter and rotor, and then all the unit unbalance vectors in the discrete vector model are added to the milling center. The numerical relationship between the milling depth and the removal of the mass unbalance vector is obtained, and the accuracy of the model is verified via comparison with the data of the simulation experiments. The complexity of the integral formula of the numerical milling model makes it difficult to apply in practice. The discrete vector model does not require integration of the numerical formula and only considers the milling area as being composed of countless discrete blocks, which greatly simplifies the process of solving the unbalance vector. In view of the different thicknesses of the tooth surface of the armature, in order to avoid damage to the armature during milling, the unbalanced vector is decomposed at the center of the tooth surface by force decomposition. The experimental results show that this proposed method can effectively improve the dynamic balancing accuracy of the micromotor armature.